2004
DOI: 10.1080/08035250410024727
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of food during the infant's first year: a study with emphasis on introduction of gluten and of egg, fish and peanut in allergy‐risk families

Abstract: These results suggest that time of introduction of gluten was not in accordance with the current recommendation. The results imply that there is a need to follow up if and how this feeding information is distributed to parents with infants and also to sharpen the information to the right target groups, otherwise implementation of preventive strategies will be less useful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
1
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 27 publications
2
15
1
1
Order By: Relevance
“…Sixty-five per cent of women in this study reported avoiding peanut during pregnancy regardless of their own or their family history of atopy. Although this advice (COT report) was only issued in the UK (Calman, 1998;Woods, 1998), other countries have also reported that some pregnant women avoided peanut during pregnancy, even though this was not recommended in their country and that this avoidance was unrelated to atopic status (van Odijk et al, 2004). Forty two per cent of the mothers in this cohort had recalled hearing about the COT advice whilst pregnant and on the basis of this advice, half of this group had changed their diets.…”
Section: Discussionmentioning
confidence: 99%
“…Sixty-five per cent of women in this study reported avoiding peanut during pregnancy regardless of their own or their family history of atopy. Although this advice (COT report) was only issued in the UK (Calman, 1998;Woods, 1998), other countries have also reported that some pregnant women avoided peanut during pregnancy, even though this was not recommended in their country and that this avoidance was unrelated to atopic status (van Odijk et al, 2004). Forty two per cent of the mothers in this cohort had recalled hearing about the COT advice whilst pregnant and on the basis of this advice, half of this group had changed their diets.…”
Section: Discussionmentioning
confidence: 99%
“…Two further studies investigated whether a family history of allergic disease had any effect on weaning practices. van Odijk et al found no difference between timing of introduction of solids or introduction of highly allergenic foods in the atopic and nonatopic families (12). In contrast, Schoetzau et al (21) found that mothers of infants with a family risk of eczema had delayed solid food feeding beyond the first 6 months more frequently than mothers of subjects without a family history.…”
mentioning
confidence: 99%
“…In addition, it is often assumed that knowledge of risk factors in childhood alone is sufficient for effective parental prevention of adverse health outcomes. However, even when parents are aware of prevention measures, they often fail to comply (Davis et al 2001;van Odijk et al 2004;Zuckerman and Duby 1985), and compliance varies significantly across ethnic groups (Flaskerud and Liu 1991;Tirosh et al 2000). These empirical trends raise two fundamental questions: to what extent can parents prevent poor child health outcomes in different ethnic and socioeconomic contexts, and what specific behaviors enable parents to prevent such outcomes to their maximum ability given specific social and economic constraints?…”
mentioning
confidence: 99%